Trabalho infantil na agricultura :sentidos produzidos pelas mês e pelos professores - Feitosa, Izabel Christina do Nascimento (2003)
Attempts to explain child labor, for the most part, have been reduced to the economic aspect, looking to establish a causal relationship between work and poverty. Without disregarding this aspect, we intend to approach this phenomenon considering other aspects that could be contributing towards its maintenance. We seek, above all, to articulate it with the concepts of disciplinary power and ideology. The present study, therefore, tries to consider these aspects with the intention of learning the reasons that the mothers and the teachers produce concerning child labor in the cultivation of vegetables. We elected these participants because we considered that child labor has been reinforced by the disciplinary institutions and proponents of ideology, the family and the school, here represented, respectively, by the mothers and the teachers. To affect this study, we created focused groups with the mothers whose children are students and work in the cultivation of vegetables in Gramorezinho (neighborhood situated in the northern part of Natal, RN) and with the teachers of the neighborhood school (Escola Lourdes Goudeiro). The discussion of the participants was handled according to the perspective of discursive practices, attempting to articulate them with the notions of ideology and disciplinary power. In general, we perceived how much ideology and discipline are immersed in the discursive practices of the participants. Whereas, even though in some moments the reference to work as being something that takes time from the child to study and play is apparent, the participants attribute great importance to child labor. Both for the teachers and for the mothers, work is something that can free the children from laziness, from becoming criminals and from using drugs. It too constitutes an important alternative to idleness and to the permanence of the child in the streets